THE TEACHERS' ROLES IN EDUCATIONAL ASPECT OF MERDEKA BELAJAR AT SCHOOLS - Kurniawati, Wahyu; Supriatna, Eka; Padli , Al; Aristanto, Aristanto; Murthada, Murthada; Firdaus , Mohamad (Dharmas Education Journal (DE_Journal), 2023)
In Indonesia, the educational system is fully controlled by the government, especially curriculum policies based on applicable laws and regulations. The main basis for designing the Kurikulum Merdeka is the Freedom to Learn philosophy which also underlies other educational policies. This research aims to provide an overview of the teacher's role in Kurikulum Merdeka Education in Schools. The type of research used is library research or literature study where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. The result of this research is that the teacher's Kurikulum Merdeka policy can carry out roles effectively to help students achieve learning goals. The teacher acts as a mover who plays an active role in pioneering change and improving the quality of education. The teacher not only designs and implements the curriculum but also becomes the link between the curriculum and students' interests. The role of the teacher in Kurikulum Merdeka is to carry out learning innovations to answer the needs of students and create a liberating learning climate. Learning innovation is expected to be able to help students to think independently, to innovate independently, to learn independently and creatively, to learn independently for happiness. The role of the teacher in learning innovation creates innovative teachers